Analisis Risiko Terhadap Keputusan Pembayaran Menggunakan Metode Shopee Paylater pada Kalangan Mahasiswa di Universitas Muhammadiyah Surakarta - Amelia Fatimah Az Zahra; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Technological developments have become increasingly sophisticated, where most activities already use digital technology. Including in transactions and payment methods that already utilize this technology. Shopeepaylater is one of the current payment methods that is carried out after purchase, or known as "Buy Now Pay Later", where users can pay in installments for a product with a certain tenor without using a card, with the aim of facilitating its use in meeting all their life needs. In addition to all the conveniences provided, it is recommended that users be more careful and understand the risks that may occur. This study aims to determine and analyze the effect of risk perception on interest in using shopeepaylater. The sample criteria used in this study were shopeepaylater users at the Muhammadiyah University of Surakarta in 2024. The data for this study used 100 questionnaires filled out by active shopeepaylater users. The analysis tool used for this study was multiple linear regression analysis. The results of this study found that it can be concluded that the variables (RW) Time Risk (X1), (RK) Performance Risk (X2), (RF) Financial Risk (X3), and (RS) Social Risk (X4) have a positive effect on (KP) Payment Decision (Y). While (RP) Psychological Risk (X5) has a negative effect on (KP) Payment Decision (Y). And the dominant factor that influences (KP) Payment Decision is (RK) Performance Risk which is indicated by the largest regression coefficient value compared to the variables (RW) Time Risk, (RF) Financial Risk, (RS) Social Risk and (RP) Psychological Risk, which is 0.787.